2007
DOI: 10.1093/ndt/gfm547
|View full text |Cite
|
Sign up to set email alerts
|

Venous stenosis in a pig arteriovenous fistula model--anatomy, mechanisms and cellular phenotypes

Abstract: These studies suggest that early and aggressive intima-media thickening (which is made up primarily of myofibroblasts) plays an important role in AV fistula stenosis in a pig model of AV fistula placement. Interventions that target the mechanisms and cellular phenotypes described in this model, may be effective in reducing the very significant morbidity and economic costs currently associated with AV fistula failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
116
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 37 publications
5
116
0
Order By: Relevance
“…These results were corroborated by Cheung and colleagues, who showed in a porcine AVG model that adventitial fibroblasts begin to differentiate into myofibroblasts and contribute to neointimal cells (43). Roy-Chaudhury and colleagues have also demonstrated that myofibroblasts contribute to venous stenosis formation in a porcine AVF model (44).…”
Section: Origins Of Neointimal Cells In Vascular Access Dysfunctionmentioning
confidence: 59%
“…These results were corroborated by Cheung and colleagues, who showed in a porcine AVG model that adventitial fibroblasts begin to differentiate into myofibroblasts and contribute to neointimal cells (43). Roy-Chaudhury and colleagues have also demonstrated that myofibroblasts contribute to venous stenosis formation in a porcine AVF model (44).…”
Section: Origins Of Neointimal Cells In Vascular Access Dysfunctionmentioning
confidence: 59%
“…Intimal hyperplasia is produced by the proliferation of vascular smooth muscle cells together with matrix deposition (31,47,51,59). While various cytokines have been implicated in this process, one that may be of particular importance is VEGF, specifically VEGF-A.…”
mentioning
confidence: 99%
“…The pathogenesis in AVFs that fail to mature (early failure) for dialysis, in contrast to AVG and late AVF failure, remains poorly understood. At a histological level early AVF failure is also characterized by aggressive neointimal hyperplasia in both animal and human models, seen as early as 1 month in animals 63,71 and 3 months in humans 64,66 . The underlying factors (upstream events) which may contribute to early AVF failure, include 4,[72][73][74][75][76][77][78][79][80][81] : (1) small diameter sizes in the vein and artery, (2) surgical injury at the time AV fistula placement, (3) previous venipunctures, (4) development of accessory veins after surgery, (5) hemodynamic shear stress at the AV anastomosis, (6) a genetic predisposition to vascular constriction and neointimal hyperplasia, and (7) pre-existing venous neointimal hyperplasia.…”
Section: Pathophysiologic Mechanisms Of Neointimal Hyperplasia Formatmentioning
confidence: 99%